Environmental Product Declarations – an extensive collection of availability, EN15804 revision and the ILCD+EPD format. Issue 1 (1st September 2022) - Stapel, E; Tozan, B; Sørensen, C; Birgisdóttir, H
Abstract: The increasing awareness on climate issues in the built environment places a greater responsibility on the different actors to map the building emissions, reduce and optimise the use of materials, and thereby lower the environmental footprint. With several countries enforcing legally binding CO2 limits to assess and benchmark the negative environmental side effects from buildings using the LCA method, it is presumable that practitioners from the industry will look for higher availability of data found from Environmental Product Declarations (EPDs). As the availability of data more than likely will increase drastically over the years, the study provides an extensive look into the world of digitalised EPDs, and how to use the format to extract a comprehensive number of EPD data. The extraction of data from the ECO Platform leads to a total of 1478 entities, and when adding EPDs from EPD Denmark this study scrutinises 1644 EPDs in total, from 4 EPD Program Operators (EPD-POs). The extraction process highlights the need for transparency and more mutual agreements in the documentation methods. Further, the study scratches the surface of the revised European EPD Standard EN15804, and what the changes and the transition will mean for the applicability and transparency in the building sector and for LCA models when the majority of emissions from GWP will increase.